Enantioselectivity Enhanced on LDH Layers in Ruthenium Catalyzed Asymmetric Hydrogenation of Acetophenone. Issue 13 (6th April 2020) - Shi, Xiufeng; Xing, Bin; Pan, Dahai; Fan, Binbin; Li, Ruifeng
Abstract: A novel heterogeneous catalyst has been developed by immobilizing Ru complexes on layered double hydroxide (LDH) via an electrostatic adsorption method. The prepared hybrid was characterized by a series of physical and chemical techniques, and the results confirmed the successful immobilization of the Ru complexes on the LDH support. The prepared heterogeneous Ru catalyst was found to be more enantioselective than the corresponding homogeneous analogue in the asymmetric hydrogenation of acetophenone and its ee value was 10% higher than that of the homogeneous analogue. Furthermore, the prepared heterogeneous catalyst could be recovered easily and reused at least six times without a significant loss in catalytic activity and selectivity. Density functional theory (DFT) computations revealed the influence of LDH layer on Ru complexes and the enantioselectivity of the immobilized Ru complexes in asymmetric hydrogenation of acetophenone. Abstract : A novel heterogeneous catalyst has been developed by immobilizing Ru complexes on layered double hydroxide (LDH) via an electrostatic adsorption method. The prepared heterogeneous Ru catalyst was found to be more enantioselective than the corresponding homogeneous analogue in the asymmetric hydrogenation of acetophenone and its ee value was 10% higher than that of the homogeneous analogue.